A combination of electrochemotherapy, gene electrotransfer of plasmid encoding canine IL-12 and cytoreductive surgery in the treatment of canine oral malignant melanoma. (February 2019) - Milevoj, Nina; Tratar, Urša Lampreht; Nemec, Ana; Brožič, Andreja; Žnidar, Katarina; Serša, Gregor; Čemažar, Maja; Tozon, Nataša
Abstract: The aim of this study was to evaluate the safety and efficacy of the combination of electrochemotherapy (ECT) with bleomycin and gene electrotransfer (GET) of plasmid encoding canine interleukin 12 (IL-12) for the treatment of canine oral malignant melanoma (OMM). Our focus was to determine the effect of the treatment on achieving local tumor control and stimulation of an antitumor immune response. Nine dogs with histologically confirmed OMM stage I to III were included in a prospective, non-randomized study. The dogs were treated with a combination of cytoreductive surgery, ECT and IL-12 GET, which was repeated up to five times, depending on the clinical response to the treatment, evaluated according to the follow-up protocol (7, 14 and 28 days after, the last treatment). One month after treatment, the objective response (OR) rate was 67% (6/9). Median survival time (MST) was 6 months and, even though the disease progressed in 8/9 patients at the end of the observation period (2 to 22 months), four animals were euthanized due to tumor-unrelated reasons. In addition, we observed a decline in the percentage of regulatory T cells (Treg ) in the peripheral blood in the course of the treatment, which could be attributed to a systemic antitumor response to IL-12 GET. The results of this study suggest that a combination of ECT and IL-12 GET may be beneficial for dogs with OMM, especially when other treatment approaches are not acceptable due to their invasiveness or cost. Highlights: Dogs with oral malignant melanoma may benefit from electrochemogenetherapy The treatment is minimally invasive and allows for a better posttreatment function Electrochemogenetherapy is inexpensive and can be performed on an outpaitent basis IL-12 gene electrotransfer is associated with a decline in regulatory T cells